2019
DOI: 10.1007/s12062-019-09254-6
|View full text |Cite|
|
Sign up to set email alerts
|

How to Measure Retirement Age? A Comparison of Survey and Register Data

Abstract: Due to an increasing heterogeneity in retirement transitions, the measurement of retirement age constitutes a major challenge for researchers and policymakers. In order to better understand the concept of retirement age, we compare a series of measures for retirement age assessed on the basis of survey and register data. We use data from Sweden, where flexible retirement schemes are implemented and register data are available. We link survey data from the Swedish Level of Living Survey with register data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…This might introduce information bias. However, a paper by Eyjólfsdóttir et al ( 2021 ) examining different definitions of retirement age, using the same materials as the current study, did not find significant differences between self-reported retirement age and retirement age attained by this current definition, nor by using different cut-offs than 50%. Another limitation is that we employ the same definition of retirement over the three decades under study, although there have been many reforms during the period that have made the retirement process more flexible over time.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…This might introduce information bias. However, a paper by Eyjólfsdóttir et al ( 2021 ) examining different definitions of retirement age, using the same materials as the current study, did not find significant differences between self-reported retirement age and retirement age attained by this current definition, nor by using different cut-offs than 50%. Another limitation is that we employ the same definition of retirement over the three decades under study, although there have been many reforms during the period that have made the retirement process more flexible over time.…”
Section: Discussioncontrasting
confidence: 49%
“…(Baumann et al 2020 ; Eyjólfsdóttir et al 2019 ; Svensson et al 2015 ). A sensitivity analysis using different cut-offs for the definition of retirement (when income from pension exceeds 30%, 40%, 60%, and 70% of annual income) did not show differences against using the 50% cut-off, giving us confidence in the above-mentioned definition of retirement (Eyjólfsdóttir et al 2021 ). As can be seen in Fig.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…In the current study, we focused on those who retired between their respective baseline assessment (1996, 2002, or 2008) and the first follow-up six years later (2002, 2008, or 2014) to increase representativeness (Wetzel, Bowen, & Huxhold, 2019). The definition of retirement differs between studies (Eyjólfsdóttir, Baumann, Agahi, & Lennartsson, 2019). In the present study, we defined retirement as withdrawing old age pensions (cf.…”
Section: Participantsmentioning
confidence: 99%